Evaluation of Stationary Phases Made by Hydrosilation of Alkynes on Silica Hydride - J. Pesek, Joseph; T. Matyksa, Maria; Salehi, Niloofar (Current Chromatography, 2015)
Four alkynes having a range of polarities and functional groups are bonded to a silica hydride surface via hydrosilation. The success of the reaction and characterization of the bonded material is determined by elemental analysis, diffuse reflectance infrared Fourier transform spectroscopy and solid state nuclear magnetic resonance spectroscopy. The retention properties of each of these stationary phases are evaluated by using both hydrophobic and hydrophilic analytes. Plots of retention time vs. mobile phase composition are used to determine whether the materials have reversed-phase, aqueous normal phase (ANP) or both types of chromatographic modes.
Keywords: Aqueous normal phase (ANP)